2013
DOI: 10.1097/bto.0b013e318297d37b
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic ACL Reconstruction in Press-Fit Technique

Abstract: Press-fit techniques for arthroscopic ACL replacement have been developed to avoid problems and complications related to the use of interference screws. Improper insertion of screws may reduce primary stability, injure the posterior femoral cortex, or displace hardware into the joint. Most techniques described use press-fit on either the femoral or tibial side. To avoid any supplemental fixation material an arthroscopic method was developed which achieves patellar tendon autograft fixation by press-fit on both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…It takes approximately 6 weeks for autograft bone blocks used during press‐fit fixation to osteointegrate [3, 42]. Since this fixation method depends on bone quality, it is suggested that press‐fit should be performed on younger, healthier individuals [24]. Moreover, fixation strength is dependent on the size of the bone block in relation to the tunnel and the mechanical properties of the bone (i.e., bone quality) [24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It takes approximately 6 weeks for autograft bone blocks used during press‐fit fixation to osteointegrate [3, 42]. Since this fixation method depends on bone quality, it is suggested that press‐fit should be performed on younger, healthier individuals [24]. Moreover, fixation strength is dependent on the size of the bone block in relation to the tunnel and the mechanical properties of the bone (i.e., bone quality) [24].…”
Section: Discussionmentioning
confidence: 99%
“…Since this fixation method depends on bone quality, it is suggested that press‐fit should be performed on younger, healthier individuals [24]. Moreover, fixation strength is dependent on the size of the bone block in relation to the tunnel and the mechanical properties of the bone (i.e., bone quality) [24]. When there is poor bone quality, it has been recommended that interference screw fixation is used [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations